Clinical assessment and diagnosis in social work practice - Corcoran, Jacqueline (Oxford University Press, 2010)
Social work and the DSM : person-in-environment versus the medical model -- Intellectual disabilities -- Pervasive developmental disorders / with Amy Wooley -- Oppositional defiant disorder and conduct disorder -- Attention-deficit/hyperactivity disorder -- Anxiety disorders -- Eating disorders -- Depression -- Substance use disorders -- Sexual disorders : pedophilia -- Bipolar disorder -- Personality disorders -- Schizophrenia and other psychotic disorders -- Cognitive disorders